Factors Influencing English Conversational Interaction Between Teachers and Students in High Schools in Dong Nai Province - Toan, Ly Ngoc (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
The main goal of this study is to improve the ability of teachers and students to converse in English in high schools in the province of Dong Nai. The study framework is based on the sociocultural theory of Vygotsky, with additional contributions from Long's interaction theory and Brown's communicative language teaching methodology. The research findings show that belonging, expectation, relationship, and motivation are four factors that have a positive and statistically significant impact on the conversational English-language interactions between teachers and students in this educational context. These findings were obtained through a survey of 148 English teachers in three high schools located in Dong Nai and subsequent data analysis using SPSS 20 software. The study's findings led the researchers to suggest a number of workable methods for improving teachers' ability to converse with learners in English. The aforementioned undertaking signifies a deliberate attempt to further progress language learning in Vietnam.